2010
DOI: 10.1159/000316063
|View full text |Cite
|
Sign up to set email alerts
|

The Endothelial Nitric Oxide Synthase Gene Is Associated with Coronary Artery Disease: A Meta-Analysis

Abstract: Introduction: Previous case-control studies have suggested that the endothelial nitric oxide synthase (eNOS) gene polymorphisms (G894T, 4b/a, T-786C) are associated with coronary artery disease (CAD). However, other studies do not confirm these relationships. The objective was to assess these relationships using meta-analysis. Methods: Databases, including Pubmed and Embase, were searched to access the relevant genetic association studies up to July 2009. Results: The meta-analysis included 56 studies, consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
5
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 98 publications
1
30
5
7
Order By: Relevance
“…A polymorphic variant of this gene in exon 7 characterized by a Glu298Asp (894G→T) polymorphism has been identified. Although the mechanism responsible for the eNOS Glu298Asp mutation that is related to endothelial dysfunction remains unknown, various studies (8,9,(54)(55)(56)(57) have determined the correlation of its genotypes and numerous associated diseases. A number of studies have identified a lower Asp allele frequency in CHD cases than in healthy controls, as the two alleles are considered to have codominant effects on eNOS levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A polymorphic variant of this gene in exon 7 characterized by a Glu298Asp (894G→T) polymorphism has been identified. Although the mechanism responsible for the eNOS Glu298Asp mutation that is related to endothelial dysfunction remains unknown, various studies (8,9,(54)(55)(56)(57) have determined the correlation of its genotypes and numerous associated diseases. A number of studies have identified a lower Asp allele frequency in CHD cases than in healthy controls, as the two alleles are considered to have codominant effects on eNOS levels.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the the MI and PCR-SSCP subgroup showed no association with the eNOS Glu298Asp polymorphism. Compared with a previous meta-analysis (8), the strength of the present meta-analysis was based on a more comprehensive search and the identification of a greater number of published studies, thereby providing more statistical power to detect the genetic effect estimates. A further sensitivity analysis confirmed that there was a significant association between the eNOS Glu298Asp polymorphism and the CHD risk among the Asian population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Активація eNOS і підвищення рівня NO спостерігаються й під впливом агоністів кальцію, а також розтягування стінки судини, руху крові та деяких інших чинників [20]. Ферменти NO-синтази, зокрема eNOS, здатні утворювати не тільки оксид азоту, але й метабо-літи оксидантного стресу: іон супероксиду та пероксид С. М. Малахова водню, а також нітрит-аніон, особливо в умовах нестачі коферментів або аргініну [24]. Отже, ферменти синтезу NO слід розглядати як складний ферментний комплекс, що синтезує різноманітні високоактивні сполуки залежно від змін функціонального стану клітини, забезпеченості її коферментами, незамінними амінокислотами та анти-оксидантами.…”
Section: мета роботиunclassified
“…The eNOS gene consists of 26 exons located on chromosome 7q36.1. It has been extensively studied in various ethnic populations for its association with several cardiovascular diseases [14][15][16][17]. Numerous single nucleotide polymorphisms and variable number tandem repeats (VNTRs) have been reported in the eNOS gene, some of which may affect gene expression, protein synthesis and enzymatic activity, including T-786C, located in the promoter region, Glu298Asp, located in exon 7, and a VNTR of 27 bp in intron 4.…”
Section: Introductionmentioning
confidence: 99%